1999
DOI: 10.2331/fishsci.65.884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Gonadal Sex Determination in Barfin Flounder <i>Verasper moseri</i>

Abstract: This time corresponds to the end of the temperature-sensitive period.These results suggest that gonadal sex was determined by temperature prior to the onset of gonadal sex differentiation in this fish.Key words: barfin flounder, sex determination, temperatureIt has been documented that sex in fish is controlled ge netically. However, many fish do not have a clear chro mosomal sex determining system,1) and therefore, genetic sex and phenotypic sex should be considered as separate en tities. Studies over the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 6 publications
5
29
1
Order By: Relevance
“…Among fish with a TL of 30mm to 100mm, the degree of gonadal development and gametogenesis depended on the TL. Since these results corresponded with the report of Goto et al (1999), the gonadal development in the barfin flounders used in the present study was normal and the degree of development of the germ cells was associated with the TL.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Among fish with a TL of 30mm to 100mm, the degree of gonadal development and gametogenesis depended on the TL. Since these results corresponded with the report of Goto et al (1999), the gonadal development in the barfin flounders used in the present study was normal and the degree of development of the germ cells was associated with the TL.…”
Section: Discussionsupporting
confidence: 75%
“…In the barfin flounder, morphological differentiation of the gonad into either an ovary or testis becomes distinguishable at a TL of 35 mm (Goto et al , 1999), and the oocytes develop into peri-nucleolus stage oocytes at a TL of 133 mm. In the present study, we first investigated the morphological changes in early oogenesis in barfin flounders with a TL of 30mm (before sex differentiation) to 100mm (perinucleolus stage oocytes exist) by light and electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns and other data summarized by Yamamoto (1999) suggest that an XX-XY system operates at intermediate temperatures, but that the sex of XX individuals is unstable and can be induced to produce male offspring, especially under conditions of extreme high temperature. Similar patterns have been reported in other flatfishes including P. lethosigma (Luckenbach et al 2003), Verasper moseri (Goto et al 1999), and Limanda yokohamae (Goto et al 2000). Kitano et al (1999) demonstrated that the creation of XX males in P. olivaceus at high temperature is associated with suppression of cytochrome P450 aromatase gene expression in the gonad, which at lower temperatures catalyzes the conversion of androgens to estrogens.…”
Section: Flatfishessupporting
confidence: 55%
“…In the observation of ovarian development in Sebastes schlegelii, it was shown that the ovarian cavity had been formed on the lateral side of the gonad on the coelomic wall side at fi rst, and then the gonad was differentiated to an ovary. The formation of the ovarian cavity has been enumerated as an initial index of ovarian differentiation in many teleost species having an ovary of type II-1 [Cichlidae: Oreochromis niloticus (see Nakamura and Takahashi, 1973); Gasterosteidae: Gaterosteus aculeatus (see Shimizu and Takahashi, 1980); Tetraodontidae: Takifugu rubripes (see Matsuura et al, 1994); Pleuronectidae: Verasper moseri (see Goto et al, 1999) . Thus, it was shown that the ovary of Sebastes schlegelii differentiated directly into the ovarian structure of type II-1 during the developmental process and did not pass through type II-3 during the ovarian developmental process.…”
Section: Discussionmentioning
confidence: 99%